Circo social: uma ação da educação física na educação não formal - Silva, Vinícius de Leon [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work is the fruitful result of the desire to conduct a collaborative investigation through Circus Arts with children and adolescents at social (vulnerability) risk. Thus, the very objective of the rese arch was to analyze and understand Social Circus action possibilities on non-formal education as a (viable) job option for Physical Education teachers. This research was developed through qualitative research using Field Notes as the main instrument for the meetings' data collection, which took place from May to December 2015. In general terms, the research was divided into three phases, the former was carried out at a state school through the Escola da Família Program, (which consists of the opening of all public schools on weekends, offering to the communities extra activities) and the latter two in Shelter Homes for adolescents. The results showed that there were some (considerable) difficulties throughout and some gaps in our society that become evident on the poor. Furthermore, the results also confirm the possibility of the Physical Education teachers' participation in other sectors of the society, through the non-formal Education perspective and the possibility of Social Circus as the (fundamental) instrument of this action

Este trabalho é fruto do desejo em realizar uma investigação participativa através das Artes Circenses com crianças e adolescentes em situação de risco. Sendo assim, o objetivo da pesquisa foi analisar e compreender as possibilidades de ação do Circo Social na Educação não formal como opção de atuação para os professores de Educação Física. A pesquisa foi desenvolvida através da investigação qualitativa, utilizando Notas de Campo como principal instrumento para coleta dos dados dos encontros que ocorreram no período de maio a dezembro de dois mil e quinze. De forma geral a pesquisa ficou dividida em três etapas, sendo a primeira Escola Estadual através do Programa Escola da Família e as outras duas em Abrigos de Acolhimento para Adolescentes. Os resultados apresentaram algumas dificuldades no percurso e algumas lacunas da sociedade que refletem sobre os desfavorecidos. Além disso, confirma a possibilidade de atuação dos professores de Educação Física em outros setores da sociedade, através da perspectiva da Educação não formal e a possibilidade do Circo Social como instrumento desta atuação
Keywords: Circos; Educação não-formal; Educação fisica; Professores - Formação; Circus